Ionization and NO production in the polar mesosphere during high-speed solar wind streams: model validation and comparison with NO enhancements observed by Odin-SMR - Kirkwood, Stella; Osepian, A.; Belova, E.; Urban, Joachim; Perot, Kristell; Sinha, K. (Annales Geophysicae, 2015)
Precipitation of high-energy electrons (EEP) intothe polar middle atmosphere is a potential source of signif-icant production of odd nitrogen, which may play a role instratospheric ozone destruction and in perturbing large-scaleatmospheric circulation patterns. High-speed streams of so-lar wind (HSS) are a major source of energization and pre-cipitation of electrons from the Earth’s radiation belts, butit remains to be determined whether these electrons makea significant contribution to the odd-nitrogen budget in themiddle atmosphere when compared to production by solarprotons or by lower-energy (auroral) electrons at higher al-titudes, with subsequent downward transport. Satellite ob-servations of EEP are available, but their accuracy is notwell established. Studies of the ionization of the atmospherein response to EEP, in terms of cosmic-noise absorption(CNA), have indicated an unexplained seasonal variation inHSS-related effects and have suggested possible order-of-magnitude underestimates of the EEP fluxes by the satelliteobservations in some circumstances. Here we use a model ofionization by EEP coupled with an ion chemistry model toshow that published average EEP fluxes, during HSS events,from satellite measurements (Meredith et al., 2011), are fullyconsistent with the published average CNA response (Ka-vanagh et al., 2012). The seasonal variation of CNA responsecan be explained by ion chemistry with no need for any sea-sonal variation in EEP. Average EEP fluxes are used to esti-mate production rate profiles of nitric oxide between 60 and100 km heights over Antarctica for a series of unusually wellseparated HSS events in austral winter 2010. These are com-pared to observations of changes in nitric oxide during theevents, made by the sub-millimetre microwave radiometer onthe Odin spacecraft. The observations show strong increasesof nitric oxide amounts between 75 and 90 km heights, at alllatitudes poleward of 60 ◦ S, about 10 days after the arrival ofthe HSS. These are of the same order of magnitude but ...